Contribuição dos sintomas do transtorno de déficit de tenção/hiperatividade para as dificuldades de aprendizagem da aritmética - Riviane Borghesi Bravo (2011)
Learning disorders are characterized by impairment in school abilities, which do not compromise intelligence as a whole, but are rather constrained to a few domains of cognition, such as language-related skills or mathematics. Among other causes, the mathematical learning disability (MLD) is often related to a specific disability in arithmetics (CID 10 F81.2) or to Developmental Dyscalculia (DD) itself. DD is estimated to be found on an average of 3% to 6% of the population at school age, being diagnosed by means of strict neurological criteria, which include the discrepancy between a child´s performance and its full potential or school grade. The diagnoses of DD calls for the exclusion of intrinsic causes, such as emotional difficulties, lack of stimuli or pedagogic failure. DD is considered a genetic disorder, whereas children with MLD are rather identified in accordance with their low performance in arithmetics, assessed by means of a standard test to which the percentile cutting-edge is generally between 35 and 25. Children with MLD do not always present with specific disorders and are part of a group characterized by its heterogeny in terms of clinical manifestations, etiology and development. The comorbidities for DD and MLD are often found, notably Dyslexia and ADHD (Attention Deficit Hyperactivity Disorder). The association between ADHD, for instance, is found in roughly 20% to 42% of the children with DD. Thus, this study investigated the incidence of ADHD in a group of 38 children with MLD, compared to 42 children in the control group. Children with MLD were chosen based on the criteria of the TDE (Test of School Performance) and assessed from neuropsychological and mathematical tasks. The ones responsible for each participant answered to a semi-structured interview K-SADS-PL as well as to the checklist for verification of behavior CBCL (Child Behavior Checklist). The results of the variance analysis (ANOVA) showed that both groups with MLD have deficit to perform the neuropsychological tasks that measure executive functioning, working memory and visuospatial abilities. It is worth noting that the group MLD + ADHD showed a lower performance when compared to the MLD group, although it was not possible to characterize a difference in cognitive profile between the groups. The Multinomial Regression Model allowedfor the analysis of the behavior-related variables together with the neuropsychological tasks. Both MLD groups showed attention impairment, assessed through the CBCL, although only the group MLD+ADHD has the school-related social competence compromised. The results achieved show that ADHD symptoms may be regarded as a worse to the mathematical learning disability